Genomic profile – a possible diagnostic and prognostic marker in upper tract urothelial carcinoma. (29th August 2021) - Grahn, Alexandra; Eisfeldt, Jesper; Malm, Camilla; Foroughi Asl, Hassan; Jaremko, Georg; Tham, Emma; Brehmer, Marianne
Abstract : Objectives: To investigate gene alterations as diagnostic and prognostic markers in upper tract urothelial carcinoma (UTUC). Patients and Methods: Patients with UTUC who underwent nephroureterectomy between 2005 and 2012 were followed until November 2020. DNA was extracted from paraffin‐embedded tumour tissue. Next‐generation sequencing using a 388‐gene panel was performed. First a blinded analysis using principal component analysis and hierarchical clustering was used to search for patterns of mutations. Then a comparative analysis using analysis of variance (ANOVA) was used to search for mutations enriched in groups of various grades, stages, and survival. In addition, careful manual annotation was used to identify pathogenic mutations over‐represented in tumours of high grade/stage and/or poor survival. Results: A total of 39 patients were included. All tumour stages and grades were represented in the cohort. The median follow‐up was 10.6 years. In all, 11 patients died from UTUC during the follow‐up. Tumour mutational burden showed a statistically significant correlation with stage, grade, and stage + grade. Grade 1, Grade 2, and Grade 3 tumours had different mutational patterns. Patients who died from UTUC had pathogenic mutations in specific genes e.g. tumour protein p53 ( TP53 ) and HRas proto‐oncogene, GTPase ( HRAS ). Patients with Ta Grade 1 tumours with a known pathogenic fibroblast growth factor receptor 3 ( FGFR3 ) mutation did not die from UTUC. Conclusion: The genetic analysis was highly concordant with histopathological features and added prognostic information in some cases. Thus, results from genomic profiling may contribute to the choice of treatment and follow‐up regimens in the future.